MEGAPOLITAN DKI JAKARTA: QUO VADIS? - Maksum, Irfan Ridwan (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
The choice to institutional development for Jakarta as Indonesian capital City can be a barometer of equity and fairness as values to whole developing nations, especially for urban development in Indonesia. If megapolis concept proposed by Sutiyoso received without reverse, then we have disease to the equity and fairness values as a nation state. The problematic situation of urban development in Jakarta is emergencies, but it is not to be un-fairness and un-equity to develop the other cities in Indonesia.